2019
DOI: 10.31236/osf.io/9dhb7
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mental fatigue might be not so bad for exercise performance after all: a systematic review and bias-sensitive meta-analysis.

Abstract: There is an ongoing debate in the scientific community regarding whether a state of mental fatigue may have a negative effect upon a range of objective and subjective measures of human performance. This issue has attracted attention from several fields, including sport and exercise sciences. It has been proposed that performing a long and demanding cognitive task might lead to a state of mental fatigue, impairing subsequent exercise performance. In the current meta-analysis, we sought to examine the influence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Nevertheless, a deficit in cognitive capacity may influence phenomenological experience more globally and potentially explain NLMF especially during endurance-based tasks [7]. Cognitively fatiguing tasks may lead individuals to perceive a subsequent task to be more effortful, resulting in an earlier cessation of the activity [98][99][100]; though again this finding is not consistent and may be small [101]. Actual fatigue (and indeed effort) is distinct from the perception of fatigue (and perception of effort) [102].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a deficit in cognitive capacity may influence phenomenological experience more globally and potentially explain NLMF especially during endurance-based tasks [7]. Cognitively fatiguing tasks may lead individuals to perceive a subsequent task to be more effortful, resulting in an earlier cessation of the activity [98][99][100]; though again this finding is not consistent and may be small [101]. Actual fatigue (and indeed effort) is distinct from the perception of fatigue (and perception of effort) [102].…”
Section: Discussionmentioning
confidence: 99%
“…Holgado et al, 2020;Martin et al, 2016;Silva-Cavalcante et al, 2018;. Though recent meta-analyses, adopting a broad inclusion criteria , extoll a small-to-moderate negative effect of mental fatigue on subsequent physical performance (Brown et al, 2020;Giboin & Wolff, 2019), others have raised concerns regarding conclusions drawn on the impact of mental fatigue on physical performance (Holgado et al, 2019;McMorris et al, 2018). The divergent conclusions offered by recent meta-analyses may be attributable to several methodological differences, including inclusion criteria (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…However, concerns remain regarding the veracity of the effect of mental fatigue on subsequent endurance performance and the putative causative mechanisms (Holgado et al, 2019;McMorris et al, 2018). For example, a large sample replication study from Holgado et al (2020) failed to replicate the negative effects of mental fatigue reported in the seminal work of Marcora et al (2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the magnitude of performance impairment is not robustly linked to the duration of the prior self-control task 5 , which conflicts with the theoretical proposition that the magnitude of the performance decrement should scale linearly with the duration of the prior self-control task 9 . In addition, a recent bias-sensitive meta-analysis of the literature suggests that initial estimates of the effects of prior selfcontrol on subsequent sports performance might be smaller than initially assumed 14 . This inconsistent body of literature limits our understanding of the relationship between self-control and sports performance.…”
Section: Self-control In Sports and Exercisementioning
confidence: 99%